Enhanced methods fulfilling early discharge criteria for total hip and knee arthroplasty patients - Ioannis Kougioumtzis; Efthymios Iliopoulos; Stylianos Tottas; Konstantinos Tilkeridis; Athanasios Ververidis; Georgios Drosos (Folia Medica)
Introduction: Enhanced recovery strategies have resulted in significant reductions in length of hospitalization and postoperative morbidity in total hip (THA) and total knee (TKA) arthroplasties. The success and safety of the arthroplasties are characterized by the establishment of evidence-based criteria, which offer safe hospitalization and postoperative care. Aim: The objective of the present survey was to investigate components related to fast-track recovery, discharge criteria, delayed discharge, complications, and readmissions. Materials and methods: The following methods were employed: the ASA grade, the Charlson index, the neuropathic pain (DN4) questionnaire, and the patient health (PHQ-9) questionnaire. Additionally, the study included an examination of comorbidities, hospitalization, era deliver discharge standards, and 90-day readmission. The visual analogue pain scale, complications, and demographics were also examined in the retrospective study for the research. The study was conducted f om November 2017 to January 2020. Results: Two hundred and thirty-five patients underwent TKA (n=134) and THA (n=101), the mean age was 68±8.7 years and BMI was 32.4±5.4 kg/m2. On average, the patients had 1.6±1.1 comorbidities, the Charlson index was 2.4±1.3 and the ASA grade was 2.1±0.5. The exit rules were attained at 1.9±0.75 days postoperatively. However, the actual infirmary care was 3.06±1.01 days, with a waiting span of 62.5% or 1.2 days. THA succeeded in departure principles more quickly (1.8 days vs. 2 days for TKA). Sex (p=0.04), age (p=0.009), and the Charlson index (p=0.046) were strongly related to the instant to fulfil the release norm in the TKA. While in THA, the length of ward stay was statistically significant and correlated with both age (p=0.05) and the Charlson index (p=0.05). In addition, the superPATH approach had a strong effect on the consummation of the delivery measures (1.48 days vs. 1.89 days for the Hardinge approach) (p=0.002) and shorter treatment (p=0.04). Conclusion: Achieving safe release goals and reducing hospitalization were associated with modifiable (superPATH approach) and unmodifiable (age, sex, and Charlson index) foretold agents. These indexes could offer reproducible results with limitation of postoperative complications, morbidity, and readmissions.